2021
DOI: 10.3390/electronics10091127
|View full text |Cite
|
Sign up to set email alerts
|

Design and Hardware Implementation of a Simplified DAG-Based Blockchain and New AES-CBC Algorithm for IoT Security

Abstract: Recently, to enhance the security of the Internet of Things (IoT), research on blockchain-based encryption algorithms has been actively conducted. However, because blockchains have complex structures and process large amounts of data, there are still many difficulties in using the conventional blockchain-based encryption algorithms in an IoT system that must have low power consumption and be ultra-lightweight. In this study, to address these problems (1) we simplified the conventional Directed Acyclic Graph (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…Moreover, IoT architecture has management service and application layers, and each component configuration will depend on the application. Many limitations come with the sensor nodes, like low bandwidth, short communication range, and limited CPU processing power, memory, and energy [ 16 ]. An IoT gateway is a central hub that lets data flow in both directions between IoT devices and sensors on one side and cloud/server computing and data processing on the other.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, IoT architecture has management service and application layers, and each component configuration will depend on the application. Many limitations come with the sensor nodes, like low bandwidth, short communication range, and limited CPU processing power, memory, and energy [ 16 ]. An IoT gateway is a central hub that lets data flow in both directions between IoT devices and sensors on one side and cloud/server computing and data processing on the other.…”
Section: Related Workmentioning
confidence: 99%
“…It has been shown that their enhancement maintains strict avalanche criteria for 53%. Lee and Sim [19] also enhanced the security of the AES-CBC algorithm for IoT devices by changing the IV and by changing the secret key periodically. Two cipher keys were combined to generate a new key used in the AES encryption.…”
Section: Related Workmentioning
confidence: 99%
“…The blockchains have two types of implementations: linear blockchain [3] and Directed Acyclic Graph (DAG) blockchain [4], which are graphically illustrated in Figure 2.…”
Section: Blockmentioning
confidence: 99%
“…On the other hand, DAG blockchain is the more modern approach, bringing advantages in scalability and computation by parallelism. In a DAG blockchain, typically, single transactions exist without grouping, where each transaction validates multiple previous transactions [4]. Blockchains rely on consensus algorithms for transaction validation and creating a new block/transaction to the blockchain.…”
Section: Introductionmentioning
confidence: 99%